Molecular epidemiology and antibiotic resistance of staphylococci other than Staphylococcus aureus in children in Cape Town, South Africa - Ocloo, Remous; Newton-Foot, Mae; Ziebuhr, Wilma; Whitelaw, Andrew Christopher (Frontiers in Microbiology, 2023)
Staphylococci other than Staphylococcusi aureus (SOSA) have emerged as a significant pathogens in healthcare settings, particularly amongin patients with indwelling devices and immunocompromised individuals. Staphylococcus epidermidis, Staphylococcus haemolyticus and Staphylococcus hominis are the most common commensal SOSA species and are implicated in infections such as endocarditis and bacteraemia. SOSA infections in neonates and children have been reported globally. Recent increases in antibiotic resistance and virulence amongst SOSA strains in clinical settings have highlighted the need to describe the reservoirs of SOSA to enable monitoring of these emerging pathogens.This study included 150 hHealthy children (n=150) from Cape Town communities. were included in this study. Stool samples were collected from each participant between 2017 and 2020. Among the participants, A total of 45 (30.0%) participants were colonized by SOSA, withof which S. haemolyticus (n=38; 25.3%) being thewas most common, followed by S. hominis (n=5; 3.3%) and Mammalicoccus sciuri (n=5; 3.3%). Out of the 77 S. haemolyticus initially isolated S. haemolyticus strains, 23 were identified as Staphylococcus borealis throughby whole genome sequencing. All S. haemolyticus isolates (n= 49) were methicillin resistant, withof which 65.3% (n = 32) harbouringed mecA.In S. haemolyticus, SCCmec type VIII(4A) was detected in 42.0% of ST9 isolates while non-mecA methicillin resistant S. haemolyticus isolates were mostly ST49 (41.1%). Additionally, 16Sixteen (50.0%). S. haemolyticus strains contained non-typeable SCCmec elements.High rates of methicillin resistance were identified amongst colonizing SOSA in Cape Town, increasing. This increases the risk of transmissionspill-over into the clinical settings. Thise study also identified a new species, (S. borealis), for the first time in Africa.